2018
DOI: 10.1021/acs.macromol.8b00451
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Tuned Microdomain Morphology and Phase-Dependent Ion Transport Anisotropy in Single-Ion Conducting Block Copolyelectrolytes

Abstract: Block copolyelectrolytes are solid-state singleion conductors which phase separate into ubiquitous microdomains to enable both high ion transference number and structural integrity. Ion transport in these charged block copolymers highly depends on the nanoscale microdomain morphology; however, the influence of electrostatic interactions on morphology and ion diffusion pathways in block copolyelectrolytes remains an obscure feature. In this paper, we systematically predict the phase diagram and morphology of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
4
41
0
Order By: Relevance
“…[ 3–5 ] Theoretical simulations and experimental results demonstrated that ion conductivity of nanostructured block copolymer electrolytes highly depends on ionic domain continuity and orientations across grain boundaries. [ 6–10 ] Among diverse morphologies, the double gyroid phases and inverse hexagonal cylinders with ion‐conductive domains as the matrix (HEX′) have attracted more interest. Owing to the interconnected three‐dimensional ion‐conductive domains, these morphologies can promote more efficient ion transport while retaining a percolated mechanical phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 3–5 ] Theoretical simulations and experimental results demonstrated that ion conductivity of nanostructured block copolymer electrolytes highly depends on ionic domain continuity and orientations across grain boundaries. [ 6–10 ] Among diverse morphologies, the double gyroid phases and inverse hexagonal cylinders with ion‐conductive domains as the matrix (HEX′) have attracted more interest. Owing to the interconnected three‐dimensional ion‐conductive domains, these morphologies can promote more efficient ion transport while retaining a percolated mechanical phase.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the interconnected three‐dimensional ion‐conductive domains, these morphologies can promote more efficient ion transport while retaining a percolated mechanical phase. [ 7,9,11 ] Considering the double gyroid phases occupy a narrow phase window in the phase diagram and their formation usually requires rigorously controlled conditions, the attention paid to the HEX′ phase has gradually increased. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A scalable modeling framework, enabled by coarse-grained (CG) MD simulations, could greatly extend the length and time scales of conventional AA-MD simulations by two orders of magnitude. [32][33][34][35] However, to the best of our knowledge, the application of CG-MD simulations to precisely model heat conduction in thermally drawn bulk polymer fibers has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%